Examining the Role of BPJS Employment Indonesia in Ensuring Social Security for Migrant Workers in Hong Kong - Shalihah, Fithriatus; Alviah, Siti (Journal of Indonesian Legal Studies, 2023)
The 2022 National Social Security Council report reveals that 67.7% of Indonesian Migrant Workers (PMI) abroad are not enrolled in the BPJS Employment program, indicating the ineffectiveness of Republic of Indonesia Ministerial Regulation No. 18 of 2018. While social security is crucial for PMIs, the current regulatory framework falls short in ensuring comprehensive protection. In response, the Indonesian Government amended the regulation in 2023, resulting in Minister of Manpower Regulation No. 4 of 2023, aiming to enhance social security for PMIs. This research assesses the implementation of Minister of Manpower Regulation No. 4 of 2023, focusing on Hong Kong. Employing an empirical juridical approach with primary and secondary data, the study investigates the attitudes of Indonesian Migrant Workers in Hong Kong. The deductive approach is used to draw conclusions, with the study’s respondents being Indonesian Migrant Workers in Hong Kong. Despite the regulatory amendment, the findings reveal limited interest among Indonesian Migrant Workers in Hong Kong to register for government-provided social security. Reluctance stems from conflicting government regulations, as workers prefer employer-provided insurance. Consequently, Indonesian Migrant Workers express a preference for the non-mandatory status of BPJS Employment, hoping to rely on employer-provided insurance without compulsory enrollment.